2012
DOI: 10.1038/aps.2012.89
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of short- and long-term zolpidem treatment on recombinant α1β2γ2s subtype of GABAA receptors in vitro

Abstract: Aim: Zolpidem is a non-benzodiazepine agonist at benzodiazepine binding site in GABA A receptors, which is increasingly prescribed. Recent studies suggest that prolonged zolpidem treatment induces tolerance. The aim of this study was to explore the adaptive changes in GABA A receptors following short and long-term exposure to zolpidem in vitro. Methods: Human embryonic kidney (HEK) 293 cells stably expressing recombinant α1β2γ2s GABA A receptors were exposed to zolpidem (1 and 10 μmol/L) for short-term (2 h da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Previous studies have also indicated that high dosages (Liappas et al, 2003) and long-term use (Vlainić et al, 2012) of zolpidem may reduce its selectivity for GABA-A receptors, and demonstrated that the anxiolytic and stimulating action of classic BZDs (Vlainić et al, 2012) may increase the likelihood of dependence. However, high dosages and long-term use of Z-drugs may result in the development of tolerance to Z-drugs, after which users may perceive that hypnotics are less effective for sleep, and must continue using hypnotics to avoid discomfort.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have also indicated that high dosages (Liappas et al, 2003) and long-term use (Vlainić et al, 2012) of zolpidem may reduce its selectivity for GABA-A receptors, and demonstrated that the anxiolytic and stimulating action of classic BZDs (Vlainić et al, 2012) may increase the likelihood of dependence. However, high dosages and long-term use of Z-drugs may result in the development of tolerance to Z-drugs, after which users may perceive that hypnotics are less effective for sleep, and must continue using hypnotics to avoid discomfort.…”
Section: Discussionmentioning
confidence: 99%
“…Long-term use and high daily dosages of hypnotics have been associated with tolerance and dependence on both BZDs (Andersen & Frydenberg, 2011;Manthey et al, 2012) and zolpidem (Liappas et al, 2003;Vlainić, Jembrek, Vlainić, Strac, & Peričić, 2012). Having a history of drug and alcohol dependence can also increase the risks of both zolpidem (Hajak et al, 2003) and BZD dependence (Manthey et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Regarding development of tolerance and dependence to benzodiazepine-site ligands after prolonged administration, diverse effects at the molecular and cellular level have been described, including receptor desensitization and changes in the number and subunit composition of surface GABAA receptors, often leading to decreased ability of benzodiazepines to potentiate effects of GABA [17,[119][120][121][122][123][124].…”
Section: Effects Of Drugs Acting At Benzodiazepine Binding Sites At Gmentioning
confidence: 99%
“…Although zolpidem is thought to be a safe hypnotic with low dependence or abuse potential (Soyka et al, 2000), numerous studies have reported that dependence or abuse may develop after taking high-dose zolpidem continuously (Victorri-Vigneau et al, 2007). Continuous zolpidem exposure can induce adaptive changes in GABA-A receptors that could be related to the development of tolerance and dependence (Vlainić et al, 2012). Meanwhile, supratherapeutic doses of zolpidem may cause complex sleep behaviors (Hwang et al, 2010) and memory loss (Liappas et al, 2003).…”
Section: Introductionmentioning
confidence: 99%